Recovery of indium from TFT and CF glasses in LCD panel wastes using sub-critical water - Yoshida, Hiroyuki; Siajam, Shamsul Izhar; Nishio, Eiichiro; Utsumi, Yasuhiko; Kakimori, Nobuaki; Feridoun, Salak Asghari (Elsevier BV, 2014)
Indium was efficiently recovered from color filter (CF) glass in LCD panel wastes using sub-critical water, which is only harmless water, at various temperatures and reaction time. By treatment in just 5 min reaction time using sub-critical water, this work achieved an outstanding 83% indium oxide recovery from CF glass and 7% from TFT glass at 360 °C. Clean and quality glass was also simultaneously recovered from CF glass. Higher exfoliation of organic multi-layers attached together with indium oxide and tin oxide was obtained over CF glass than that over TFT glass. Furthermore, indium did not dissolve in the liquid-phase but existed as indium oxide attached with the organic multilayers that were removed from CF glass. Since indium oxide was readily separated from CF glass, it was easily recovered from the liquid-phase by filtration. The amount of indium recovered was dependent on the sub-critical water reaction temperature. Sub-CW treatment at 5 min reaction time resulted in the highest indium recovery from CF glass. Thus, it was proven that sub-critical water treatment was a promising method for indium recovery from CF glass in LCD wastes.